Analysis of Electronic Money in Indonesia - Ika Rahayu; Rusiadi Rusiadi; Dewi Mahrani Rangkuty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Increasingly advanced technology currently encourages people to make transactions using electronic money (e-money). Currently, more and more Indonesia people are using electronic money, this can be seen from the volume of electronic money transactions which is increasing from year to year. People prefer to make transactions using electronic money because it is easier to transact with traders. This research aims to analyse the variables of interest rates, inflation, money supply, e-money and electronic money transactions in Indonesia. The type of research is quantitative analysis using secondary data from 2011 to 2021 with quarterly annual data take from Bank Indonesia (BI), World Bank and BPS (Central Statistics Agency). The analysis method used is VAR (Vector Autoregressive) and refined with Forecast Error Variance Decomposition (FEVD) analysis. The results of the VAR analysis show that there is a contribution to the variable itself and other variable. From the estimation results, it turns out that there is a reciprocal relationship between one variable and another variable, or in other words, all variable, namely the variable Inflation, JUB, E-Money, Interest Rate and Elecronic Money Transaction contribute to each other. The results of the FEVD analysis show that not all variables contribute to the variable itself.